1986
DOI: 10.1002/ana.410190310
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing and speech production in Parkinson's disease

Abstract: Videofluoroscopy was used to examine movement patterns during swallowing and speech production in 6 parkinsonian subjects and 6 age-matched controls. Motility patterns for liquid and semisolid swallows were documented. We performed temporospatial analyses of oropharyngeal structures, particularly the velum, which is prominently involved in both motor speech production and swallowing. Differences were found between groups and conditions. All of the parkinsonian subjects exhibited abnormal oropharyngeal movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
175
3
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(189 citation statements)
references
References 23 publications
9
175
3
2
Order By: Relevance
“…Of note, such impairment was much more prominent during reflex than voluntary coughing. On one hand, the results demonstrate that Parkinson's disease features a generalised impairment of autonomic reflexes such as, for instance, the pharyngeal phase of swallowing [18] and the cough reflex. On the other hand, the findings also suggest that the evaluation of the cough motor pattern provides useful information on the central mechanisms subserving this crucial reflex response; in more details, it seems likely that impaired expiratory muscle recruitment during voluntary and, more markedly reflex cough reflect one of the most prominent functional disturbances of patients with Parkinson's diseases, i.e slowness of movement that is ongoing, or bradykinesia [7].…”
Section: The Cough Job: Expulsionmentioning
confidence: 94%
See 3 more Smart Citations
“…Of note, such impairment was much more prominent during reflex than voluntary coughing. On one hand, the results demonstrate that Parkinson's disease features a generalised impairment of autonomic reflexes such as, for instance, the pharyngeal phase of swallowing [18] and the cough reflex. On the other hand, the findings also suggest that the evaluation of the cough motor pattern provides useful information on the central mechanisms subserving this crucial reflex response; in more details, it seems likely that impaired expiratory muscle recruitment during voluntary and, more markedly reflex cough reflect one of the most prominent functional disturbances of patients with Parkinson's diseases, i.e slowness of movement that is ongoing, or bradykinesia [7].…”
Section: The Cough Job: Expulsionmentioning
confidence: 94%
“…The importance of abdominal muscles in the production of the cough expulsive force is well known, and it has been confirmed by many electromyographic (EMG) studies [6][7][8][9][10] . For instance, several human investigations have shown activation of the rectus abdominis, internal oblique, external oblique, and transversus abdominis muscles during voluntary cough [16][17] Furthermore, abdominal muscle activation has been found to be proportional to cough flow rate, and a linear relationship has been demonstrated between increases in EMG activity and voluntary cough flow rates [18,19] In addition to abdominal muscles, EMG bursts over the latissimus dorsi and pectoralis major muscles have been demonstrated during voluntary cough efforts in healthy volunteers and tetraplegic subjects in whom corticospinal abdominal inputs were interrupted [20,21] At variance with the inspiratory and compressive phases, several comparisons of the motor features of the expulsive efforts of cough produced voluntarily and reflexly in the same subjects can be found in the literature. A recent study analysed motor activation patterns of voluntary and reflex cough adjusted for flow rates.…”
Section: The Cough Job: Expulsionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent tracing studies in monkey Jurgens, 2003, 2005) have demonstrated dense reciprocal connections between the laryngeal motor cortex and the putamen and thalamus, yet subcortical control systems and their modulation of cortical and the brain stem centers are virtually unexplored. Significant voice and swallowing deficits seen in Parkinson disease suggest that other regions besides the cortex and medulla are critical to normal laryngeal control for speech and swallowing (Logemann et al, 1977;Robbins et al, 1986). Improved knowledge of the basal ganglia control of the laryngeal musculature might allow for exploration of various neurotransmitter systems to improve laryngeal function in cough, swallow, voice, speech and respiration.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%